Zamyatin's We and the Idea of the Dystopie - Margaret Lael Mikesell; Jon Christian Suggs (Studies in 20th & 21st Century Literature, 1982)
An examination of We clarifies conventions for the dystopic novel even as it reveals that We transcends those conventions. Under the surface text, which presents a narrative of political and "romantic" struggle, lie subtexts exploring the personal and ideological implications of the conflict between reason and emotion. Analysis of these texts, seen in a New Comedy framework informed by elements of irony and romance, demonstrates that on every level the novel fails to reach comic resolution. Moreover, it is this very failure that marks the departure of We from the conventions of the dystopic novel. Like Brave New World and 1984, We contains satire and an obvious dystopia. However, it does not contain the other convention defining the genre—a recognizable and accessible moral norm. Rather, it depicts two dysfunctional Utopian systems in conflict. In transcending the conventions of the dystopic novel and in offering only partial resolution outside of its own flawed and mutually exclusive worlds, We explores the contradictions of the "modern" experience.
Keywords: dystopic novel; dystopia; ideology; identity; reason; emotion; Zamyatin; we; Brave New World; 1984; satire; utopian; modern experience